2006
DOI: 10.1590/s0100-204x2006001000003
|View full text |Cite
|
Sign up to set email alerts
|

Whitefly, aphids and thrips attack on cabbage

Abstract: -The objective of this work was to investigate the relationships between predators and parasitoids, leaf chemical composition, levels of leaf nitrogen and potassium, total rainfall, relative humidity, daylight and median temperature on the intensity of whitefly, aphid, and thrips attack on cabbage. Whitefly, aphids and thrips population tended to proliferate in the final stage of plant or reached a peak population about 40 days after plantation. The whitefly and thrips tended to increase with an increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The GBM mixture could, therefore, be used as a potential companion or field boundary crop in cucurbits to enhance beneficial insect populations for the control of sucking insect pests, especially SLW. Leite et al (2006) reported that spiders were limiting factors for population increases of SLW.…”
Section: Discussionmentioning
confidence: 99%
“…The GBM mixture could, therefore, be used as a potential companion or field boundary crop in cucurbits to enhance beneficial insect populations for the control of sucking insect pests, especially SLW. Leite et al (2006) reported that spiders were limiting factors for population increases of SLW.…”
Section: Discussionmentioning
confidence: 99%
“…They can quickly lower pest populations in several crop species (Yeargan, 1975;Nyffeler et al, 1994). Spiders have been considered as limiting factors for population increases of SLW (Leite et al, 2006) and the reduction of SLW numbers in the present studies may be due in part to the presence of spiders.…”
Section: Discussionmentioning
confidence: 65%
“…Trichome density was determined on one expanded leaf from the apical, medium, and bottom canopy strata of 10 plants per crop (three leaves per plant), which were collected monthly in Guidoval and Viçosa, prepared on slides, and the trichome assessed (Leite et al, 2001a;2001b;2002a;2002b;2002c;2005a;2005b;2005c;2006a;2011). Leaf N and K levels were determined monthly in the laboratory from one expanded leaf of the upper parts of 10 plants per crop in both municipalities.…”
Section: Methodsmentioning
confidence: 99%
“…These leaves were dried and ground, K was determined with a flame photometer, and N analyzed by the Nessler method. Fully expanded apical leaves of 10 plants per crop were sampled monthly in both municipalities by gas chromatography/mass spectrometry (GC/MS) and hexane analyses were performed as in Leite et al (2001a;2001b;2002a;2002b;2002c;2005a;2005b;2005c;2006a, 2011. Morphological, nutritional, and chemical analyses were made with three independent monthly evaluations for each plantation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation